Gamification in Technology-Based English Language Teaching: Enhancing Student Engagement at Baitul Qur’an Al Askar Kota Kendari - Sachrul Muh. Saleh; Sam Hermansyah; Titin Rahmiatin Rahim; Yuliyanah Sain (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
The integration of gamification into technology-based English language teaching (ELT) has emerged as a promising strategy to address low student engagement in EFL classrooms. This study investigated the effectiveness of gamification elements embedded in digital platforms to enhance student engagement among tenth-grade students at Baitul Qur’an Al Askar Madrasah Aliyah. Employing a quasi-experimental pre-test and post-test design, the research involved 36 students who participated in gamified English lessons utilizing platforms such as Kahoot! and Quizizz. Gamification elements, including points, badges, leaderboards, and instant feedback, were integrated into vocabulary, grammar, and speaking activities over a 12-week intervention period. Student engagement was measured using a validated 5-point Likert-scale questionnaire adapted from the Student Engagement Instrument, supplemented by classroom observations and semi-structured interviews. Quantitative analysis using paired-sample t-tests revealed a statistically significant increase in overall engagement scores from pre-test (M = 3.18, SD = 0.75) to post-test (M = 4.47, SD = 0.62), t(35) = -8.76, p < .001. Qualitative findings further indicated heightened motivation, active participation, and collaborative learning. The study concludes that gamification in technology-based ELT effectively boosts student engagement in Islamic senior high school settings. Practical implications for EFL teachers and suggestions for future research are discussed.